Development of internet-based instrumentation system for study of the hall effect. - Abas, Ariffin (2011)
The computer together with Lab View software can be used as automatic data acquisition system. This project deals with the development of a computer interfacing technique (automation system) for the study of Hall effect and converting the existing automation system into web based automation system. The drive board RS 217-3611 with PCI 6025E card and stepper motor RS191-8340 with resolution of 0.1mm was used to move a pair of permanent magnet backward and forward against the sample. The General Interface Bus (GPIB) card interfaces together with digital nano voltmeter/Current source and Tesla meter using serial port RS232 interface are used to measure potential difference/current supply and magnetic field strength respectively. These systems (hardware interfacing) were able to log, store and plot the graph of Hall voltage as a function of magnetic field strength which can be viewed at the front panel display of the Lab View programming. Hall effect measurement at room temperature on Copper (Cu) and Tantalum (Ta) showed negative and positive sign Hall coefficient indicating that the systems have electron or hole charge carriers respectively. These phenomena can be explained using Free Electron Model (FEM) and Energy Band Theory (EBT). The Hall effect for YBa2Cu3-xTixO7-δ system (where by x=0.00, x=0.01, x=0.03 and x=0.05) was found to show positive sign Hall coefficient making this system a predominantly hole carrier at room temperature. The parameters such as Hall coefficient, drift velocity, conductivity, mobility, and charge carrier concentration were also automatically displayed on the front panel of Lab View programming and compared with previous value by other researchers and Lakeshore Hall effect measurement system model 7604. The Web based automation system can be remotely controlled and monitored by users in another location by using only their web browsers. This is achieved by programming the server computer to load Java Applets containing the users interface required to control the automation system into the remote user’s web browser and data can be remotely acquired through File Transfer Protocol (FTP). In addition, video conferencing through Net Meeting program has been used to provide audio and video feedback, with web camera mounted on moveable platform so that the user can control viewing angle. The obvious advantage of this system is in the field of education. Student can viewing and control physics experiments carried out live over internet and also participate over conventional Web browsers in real time. In this project, the apparatus that has been developed to measure the Hall effect at room temperature is simple, cheaper, mobile, easy to handle and able to give accurate result as compared to the previous researcher. This system which has not been developed previously can now be developed as an affective teaching aid.